Cote d'Ivoire : From Crisis to Sustained Growth -- Priorities for Ending Poverty and Boosting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2015)
This systematic country diagnostic is structured in two main parts, one backward looking and the other forward looking. The backward-looking analysis aims to draw lessons on the determinants of poverty and sustainable and inclusive growth from (a) stakeholder consultations; (b) a poverty profile; (c) a jobs profile; and (d) a review of Cote d’Ivoire’s experience, and a comparison with Ghana and Sri Lanka, countries with similarities to Côte d’Ivoire, but with different growth trajectories. The poverty analysis shows that over the past 25 years, poverty has deepened considerably, in particular in rural areas in the North and West. While the fall in cocoa prices played an important role, consequences of the price shock were amplified by political and social crisis and cuts in social expenditure. The main employment challenge faced by Cote d’Ivoire is a high concentration of employment in low-productivity occupations, such as agricultural and non-agricultural self-employment, particularly among the poor, women and those living in rural areas. Very few individuals hold formal wage jobs, and those who do are concentrated among the more educated in urban areas. In the near- and medium term, job creation will benefit significantly from growth in the self-employment and micro-enterprise sectors. The analysis concludes that Cote d’Ivoire’s poor performance can be attributed to its response regarding four sets of policy issues: (a) lack of agricultural development and diversification; (b) lack of structural transformation into agro-business and non-agrobusiness led by the private sector; (c) inequitable social policies; and (d) lack of good governance. Based on this analysis, the forward-looking part outlines Côte d’Ivoire’s strategic pathways out of poverty, better jobs creation through private sector-led growth and human capital development, and the prerequisites for achieving those goals. For better jobs creation, the main pathways are increased agricultural productivity and diversification into agribusiness and other types of industries. Addressing constraints under these pathways, in particular access to finance, will also promote microenterprises and self-employment. For human capital development, the main pathways are increased and higher quality social spending and an effective social safety net. The last chapter prioritizes key binding constraints and discusses knowledge gaps.